Pengaruh Digital Marketing dan Kualitas Pelayanan Terhadap Keputusan Pembelian pada Café Unsilent Bandar Lampung - Pratiwi, Tyas Cindi; M, Evi Meidasari; Bakti, Umar (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
Cafe Unsilent Bandar Lampung offers a cafe concept to visitors. Apart from providing food and drinks, Cafe Unsilent Bandar Lampung also offers a unique natural atmosphere so that visitors are really pampered by the atmosphere at Cafe Unsilent Bandar Lampung. The aim of this research is to find the influence of digital marketing and service quality on purchasing decision making at Cafe Unsilent Bandar Lampung . the type of research used in this research is quantitative research. The research sample was determined using Non-Probability Sampling with a sample of 30 respondents, namely visitors to Cafe Unsilent Bandar Lampung. From the results of the research that has been carried out, it is clear that Digital Marketing and Service Quality have a partial influence on purchasing decision making at cafe unsilent bandar lampung. Together Digital Maarketing (X1) and Service Quality (X2) have an influence of 86,1 % on purchasing decision making. Cafe Unsilent Bandar Lampung. Meanwhile, the remaining was influenced by other factors not examined in this study.